2022
DOI: 10.3390/toxics11010007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polychlorinated Dibenzo-p-dioxins, Polychlorinated Dibenzofurans, and Dioxin-like PCBs on Teeth and Bones in Animals and Humans

Abstract: Bone metabolism is regulated by endocrine systems, so people exposed to polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) may suffer adverse effects on bones and teeth. We reviewed previous publications in which effects of PCDD/Fs and dioxin-like polychlorinated biphenyls on the teeth and bones of animals and humans were found. The aim was to identify future research directions, particularly for epidemiological studies of populations exposed to PCDD/Fs in the environment. Exposure of fetuses to PCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
(97 reference statements)
0
1
0
Order By: Relevance
“…Takiguchi et al [ 8 ] reviewed previous publications in which the effects of PCDD/Fs and dioxin-like PCBs on the teeth and bones of animals and humans were found to identify future research directions, particularly for epidemiological studies of populations exposed to PCDD/Fs in the environment. Previously, it has been reported that exposure of fetuses to PCDD/Fs may affect odontogenesis, particularly enamel formation in human and animals.…”
mentioning
confidence: 99%
“…Takiguchi et al [ 8 ] reviewed previous publications in which the effects of PCDD/Fs and dioxin-like PCBs on the teeth and bones of animals and humans were found to identify future research directions, particularly for epidemiological studies of populations exposed to PCDD/Fs in the environment. Previously, it has been reported that exposure of fetuses to PCDD/Fs may affect odontogenesis, particularly enamel formation in human and animals.…”
mentioning
confidence: 99%